Moving Toward Implementation of Responsible Artificial Intelligence in Health Care: The European TRAIN Initiative - van Genderen, Michel E; Kant, Ilse M J; Tacchetti, Carlo; Jovinge, Stefan (JAMA : the journal of the American Medical Association, 2025)
This Viewpoint discusses the Trustworthy and Responsible AI Network Europe (TRAIN-Europe) consortium, an effort of medical and AI experts to oversee, develop, and share ethical practices through collaboration and technological solutions designed to implement responsible AI practices.